Research Trends and Directions on Real Estate Investment Trusts’ Performance Risks - Okoro, Chioma; Ayaba, Marie Mangwi (Sustainability, 2023)
The status of real estate investment trusts (REITs) rose in investment decisions and research since 2008, after the global financial crisis (GFC) and the surge in REITs. However, the sector is still in its infancy in most emerging markets and African countries. The current study examines the literature on the performance of REITs and the related risks using bibliometric and content analyses. The study’s objectives were to determine the research trends on the topic since 2008, the prominent authors, countries, and sources, the knowledge trend and themes associated with the existing research to date, and future or new directions for research. Materials from 2008 to 2022 indexed in the Scopus database were retrieved and visualised using VOSviewer software. The findings revealed that publications were mostly in Australia, Italy, Singapore, and Canada. The co-authorship links were dominant among the Australian authors. The themes that emerged were centred around REITs’ portfolio measurement, risk management in diversified portfolios, capital structure, efficiency measurement, corporate governance, portfolio risk assessment, portfolio construction, and asset allocation strategies. The findings are envisaged to be beneficial in informing further research directions on the subject. The performance threats are also highlighted for industry stakeholders’ decision-making and strategic planning around REITs’ sustainability.